A review of literature of a functional, congenital intrathoracic kidney - Sahil Sabharwal; Brandyn Young; Sarat Sabharwal; Kristen Brandon; Sarah Assem (Journal of Cardiothoracic Surgery)
Abstract Introduction The rarest form of renal ectopia, the thoracic kidney, has been documented in only about 200 cases worldwide. There are four recognized causes of congenital thoracic renal ectopia: renal ectopia with an intact diaphragm, diaphragmatic eventration, diaphragmatic hernia, and traumatic diaphragmatic rupture. This condition often presents as an incidental finding in asymptomatic patients. The following is a report of mediastinal renal ectopia in a 52-year-old male patient. Case description The patient is a 52-year-old male who presented on admission with gastrointestinal bleeding, reporting melena and fatigue. On admission, laboratory workup revealed a hemoglobin level of 9.2 g/dL (normal: 13.5–17.5 g/dL) and a hematocrit of 28% (normal: 41–50%), indicating mild anemia. A stool guaiac test was positive for occult blood. Initial resuscitation with intravenous fluids stabilized the patient, and he did not require blood transfusion. Upper endoscopy (EGD) and colonoscopy were performed but did not identify a clear source of bleeding. Given the resolution of symptoms and stable laboratory values during hospitalization, the bleeding resolved spontaneously. However, a CT scan of the abdomen and pelvis incidentally showed a 4 × 4 cm soft tissue attenuation in the right paraspinous fat in the lower thoracic spine adjacent to the right hemidiaphragm. A follow-up MRI measured the mass to be 3 cm × 7.5 cm × 7.6 cm and showed the mass to resemble a kidney. The MRI also demonstrated two anatomically normal kidneys, as well. A previous CT angiogram of the chest and lower back 2 years prior showed a similar finding that measured 37 mm × 60 mm × 70 mm and is presumed to be the same mass. According to the radiology report, the findings are consistent with an ectopic thoracic kidney that is unchanged in size. Both Urology and Cardiothoracic Surgery were consulted. Due to the pathology being asymptomatic, both services have agreed to forego biopsy and to monitor the patient in the outpatient setting. Discussion A congenital ectopic thoracic kidney is the rarest form of kidney ectopia. IV urography used to be the diagnostic modality of choice; however, it has recently been replaced by less invasive imaging methods, such as ultrasonography or computed tomography. In normal urogenital development, the embryonic folds begin to form the urinary tract and urogenital ridge in week four. The urogenital ridge subsequently divides into the nephrogenic ridge and gonadal cord. The nephrogenic ridge then begins to form three kidneys: pronephros, mesonephros, and metanephros. Out of these three structures, only the metanephros progresses to fully developed human kidneys. The embryologic kidneys originally lie close together in the sacral region. But as the abdomen expands during weeks six through nine, the kidneys ascend and are drawn apart to their final location in the lumbar region. In some cases, the kidney may herniate into the hemithorax via a diaphragmatic defect known as a Bochdalek hernia. However, in our patient, the kidney metanephric cells migrated past the diaphragm prior to diaphragmatic closure, which resulted in a functional kidney located in the thorax without any associated diaphragmatic defect. Due to the patient’s asymptomatic nature, Cardiothoracic Surgery and Urology collectively decided not to proceed with surgical exploration and possible nephrectomy of the ectopic kidney due to the overwhelming risks, and have elected to observe and monitor the patient’s clinical course. Conclusion In conclusion, we have presented a rare case of a congenital renal ectopia that was incidentally discovered in 52-year-old male who presented with a gastrointestinal bleed, which was later confirmed with a CT scan and MRI. Given how rarity of this pathology, a multidisciplinary approach, involving medicine, urology, and cardiovascular surgery was needed. Given the pathologies asymptomatic nature, the decision to continue close observation and follow-up was chosen, especially considering the risk of invasive surgical intervention. Further research and documentation is essential not only to provide optimal care in this patient, but to better understand the pathophysiology and management of renal ectopia for future patients.